2015
DOI: 10.1002/2327-6924.12200
|View full text |Cite
|
Sign up to set email alerts
|

Shared medical appointments for patients with diabetes: Glycemic reduction in high-risk patients

Abstract: Purpose To assess the impact on glycemic control (A1c, %) in a primary care urban Veterans Affairs (VA) shared medical appointments (SMAs). Data sources A retrospective pretest/posttest study included all patients who had attended ≥1 SMA from 4/06 to 12/10. A1cs 810 days pre‐ and postinitial SMA were obtained from 90‐day time periods. A1c levels were averaged within patient in these 90‐day intervals and data were aggregated based upon corresponding time intervals. Conclusions Of 1290 individuals seen in SMAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Originally developed by Caballero (6), SMAs are defined as: “… consecutive individual medical visits carried out in a supportive group setting of similar patients where all can listen, interact, and learn .” SMAs are group or cluster medical consultations (7), carried out sequentially, where approximately 8–15 patients with the same chronic condition are seen by a physician and an interdisciplinary team of health-care professionals over a 60- to 120-min time period (8). This allows physicians to deliver the same level of care to multiple patients at the same time, thereby maximizing available resources (6).…”
Section: Introductionmentioning
confidence: 99%
“…Originally developed by Caballero (6), SMAs are defined as: “… consecutive individual medical visits carried out in a supportive group setting of similar patients where all can listen, interact, and learn .” SMAs are group or cluster medical consultations (7), carried out sequentially, where approximately 8–15 patients with the same chronic condition are seen by a physician and an interdisciplinary team of health-care professionals over a 60- to 120-min time period (8). This allows physicians to deliver the same level of care to multiple patients at the same time, thereby maximizing available resources (6).…”
Section: Introductionmentioning
confidence: 99%
“…Veterans have reported satisfaction and increased well‐being with SMA management for health issues such as smoking cessation, weight management, and diabetes (Cohen, Hartley, Mavi, Vest, & Wilson, ). SMA diabetes management programs utilizing NPs within the VA have documented successful improvements in glycemic control as measured by a reduction in hemoglobin A1c (HbA1c; Tokuda et al., ; Watts et al., ). Watts et al.…”
Section: Vha Interprofessional Team‐based Care and Population Health mentioning
confidence: 99%
“…Studies have shown that shared medical appointments (SMAs) improve glycemic control in diabetic patients . An SMA is defined as “a model of care which involves multiple patients being seen as a group.” The structure of the SMA looks different in each study but generally combines a standard medical appointment with education and peer to peer discussion to improve self‐management of a chronic disease . Shared appointments have proven to increase knowledge of medical conditions as well as improve self‐care .…”
Section: Introductionmentioning
confidence: 99%